Relationship Between Age, Coffee Consumption and Smoking with The Incidence of Gastro Esophageal Reflex Disease (GERD) - Putri, Annisa Zahara; Pramana, Kadek Dwi; Wulandari, Made Ayu Mirah; Khairunnisai, Khairunnisai (Jurnal Biologi Tropis, 2025)
One of the most prevalent illnesses in the world is gastroesophageal reflux disease, or GERD. In addition to sleep patterns, eating habits, such as the amount and timing of meals, as well as the acidity of food, can also lead to GERD. The purpose of this study is to investigate how smoking, coffee intake, and age relate to the prevalence of GERD in the province of NTB, particularly in West Lombok Regency. This study used a quantitative approach and a cross-sectional study design. The Chi Square test was employed for statistical analysis after univariate and bivariate data analysis. The results showed that 52% of respondents were women and 48% of respondents were men. 67% of respondents claimed not to have GERD, while 33% reported having it. There is a substantial correlation between age, coffee consumption, and smoking and the occurrence of GERD at Patut Patuh Patju Hospital in West Lombok. The Patut Patuh Patju Hospital in West Lombok has concluded that smoking, coffee use, and age are associated with GERD.